Viewing generic prescription medicines in Australia - a consumers' perspective - Liang, Johan; Phau, Ian (School of Marketing, Curtin Business School, 2010)
This paper investigates consumer perception on generic medicines in Australia. Specifically, it examines how consumer concern and consumer knowledge about counterfeit medicines influence attitudes towards generic prescription medicine and willingness to pay more for branded prescription medicines. A research model is developed together with an agenda of nine hypotheses that contain consumer concern, consumer knowledge, attitude towards PGM, willingness to pay more for branded PM, consumer trust in internet shopping, and likelihood not to purchase PGM from legitimate drug store or Internet. Theory of Reasoned Action (TRA) is used to explain the results based on the proposed research model in this study. Mail surveys are implemented to reach mature age population as the segment of the sample. Other relationship within the model and a number of implications for businesses will be discussed, suggestions for future research are reviewed and the main contributions of the study will also be delineated.